ALIH AKSARA DAN ALIH BAHASA TEKS CERITA NABI IBRAHIM AS: Tinjauan Filologis - Helizar Helizar; Hasanuddin WS Hasanuddin WS; Amril Amir (Faculty of Languages and Arts, Universitas Negeri Padang, 2013)
This article was written to (1) describe the translation of story about Ibrahim prophet at text Story of Prophets version Azhari Alkhalidi Rahmatullah, (2) describe change language of story about Ibrahim prophet at text Story of Prophets version Azhari Alkhalidi Rahmatullah. The data of this study were story about Ibrahim prophet at text Story of Prophets version Azhari Alkhalidi Rahmatullah. The text was got from field research. The text was data processing by four step, is roundup of data, describe of the text, translation, and change language. The finding of the study is avalaible of text about Ibrahim prophet at text Story of Prophets version Azhari Alkhalidi Rahmatullah in Latin script and Indonesian language and more words that indicate old language charactheristic. Kata kunci: alih aksara, alih bahasa, teks, filologis